Technological innovation for cyber-physical systems : 7th IFIP WG 5.5/SOCOLNET Advanced Doctoral Conference on Computing, Electrical and Industrial Systems, DoCEIS 2016, Costa de Camparica, Portugal, April 11-13, 2016, proceedings /: 7th IFIP WG 5.5/SOCOLNET Advanced Doctoral Conference on Computing, Electrical and Industrial Systems, DoCEIS 2016, Costa de Camparica, Portugal, April 11-13, 2016, proceedings. (2016) - Unknown
No abstract available